2006
DOI: 10.1103/physrevb.73.014529
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Andreev bound states inYBa2Cu3O7xAu

Abstract: We report on Josephson and quasiparticle tunneling in YBa 2 Cu 3 O 7-x (YBCO)/Au/Nb ramp junctions of several geometries. Macroscopically, tunneling is studied in the ab-plane of YBCO either in the (100) and (010) direction, or in the (110) direction. These junctions have a stable and macroscopically well defined geometry. This allows systematic investigations of both quasiparticle and Josephson tunneling over a wide range of temperatures and magnetic fields. With Nb superconducting, the proximity gap induced … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
19
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 31 publications
(74 reference statements)
2
19
0
Order By: Relevance
“…1 19 It was found that all observed features are consistent with a convolution of density of states with broadened ZES formed at the YBa 2 Cu 3 O 7−␦ / Au/ Nb junction interfaces. 19 Here, we only summarize some of the most important findings from a qualitative point of view. We observed the same qualitative picture independent of the tunneling direction.…”
supporting
confidence: 57%
See 3 more Smart Citations
“…1 19 It was found that all observed features are consistent with a convolution of density of states with broadened ZES formed at the YBa 2 Cu 3 O 7−␦ / Au/ Nb junction interfaces. 19 Here, we only summarize some of the most important findings from a qualitative point of view. We observed the same qualitative picture independent of the tunneling direction.…”
supporting
confidence: 57%
“…As our previous report showed, 19 as far as quasiparticle tunneling is concerned, there is a good quantitative agreement between the measured conductance spectra and calculations made on the basis of an S d IS s tunnel junction model using quasiclassical techniques. Looking into the Josephson tunneling, in the frame of a Green's function formalism J 2 is calculated by integrating over all transverse wave vectors, 9 and YBCO, ␦Ј͑E͒ is the derivative of the Dirac delta function, and ␣ is the angle between a reflected wave and the normal to the junction interface.…”
mentioning
confidence: 66%
See 2 more Smart Citations
“…The ABS shows up as a zero bias conductance peak of tunneling spectroscopy [6][7][8]10 , and through the study of tunneling spectroscopy of high T c cuprates [11][12][13][14][15][16][17][18][19][20] , it has been established that a dispersionless zero energy ABS 7 is generated for d xy -wave superconductors. The existence of the ABS influences seriously interface and surface properties [21][22][23][24][25][26] .…”
Section: Introductionmentioning
confidence: 99%